Candida and cardiovascular implantable electronic devices: a case of lead and native aortic valve endocarditis and literature review. Issue 11 (25th September 2015) - Glavis‐Bloom, Justin; Vasher, Scott; Marmor, Meghan; Fine, Antonella B.; Chan, Philip A.; Tashima, Karen T.; Lonks, John R.; Kojic, Erna M.
Summary: Use of cardiovascular implantable electronic devices (CIED), including permanent pacemakers (PPM) and implantable cardioverter defibrillators (ICD), has increased dramatically over the past two decades. Most CIED infections are caused by staphylococci. Fungal causes are rare and their prognosis is poor. To our knowledge, there has not been a previously reported case of multifocal Candida endocarditis involving both a native left‐sided heart valve and a CIED lead. Here, we report the case of a 70‐year‐old patient who presented with nausea, vomiting, and generalised fatigue, and was found to have Candida glabrata endocarditis involving both a native aortic valve and right atrial ICD lead. We review the literature and summarise four additional cases of CIED‐associated Candida endocarditis published from 2009 to 2014, updating a previously published review of cases prior to 2009. We additionally review treatment guidelines and discuss management of CIED‐associated Candida endocarditis.